1982
DOI: 10.3382/ps.0612129
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Immune Response Between Two Lines of Chickens Selected for Differences in the Weight of the Bursa of Fabricius

Abstract: Experiments were designed to compare antibody-mediated immunity in two lines of 5-month-old chickens previously selected for a large or small bursa. After receiving a primary or secondary challenge with sheep-red-blood cells, bovine serum albumin, or dinitrophenyl, birds from the small bursa line (SBL) were significantly more efficient antibody producers than birds from the large bursa line (LBL). However, Immunoglobulin G synthesis by SBL birds was significantly lower than in LBL birds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(33 citation statements)
references
References 9 publications
2
29
0
Order By: Relevance
“…These results are in agreement with those obtained by Ibrahiem et al [15] who reported that bursa weights were magnified by feeding onion to broiler muscovy ducks. Onions have a mode of action which is similar to antibiotics.…”
Section: Immunitysupporting
confidence: 83%
“…These results are in agreement with those obtained by Ibrahiem et al [15] who reported that bursa weights were magnified by feeding onion to broiler muscovy ducks. Onions have a mode of action which is similar to antibiotics.…”
Section: Immunitysupporting
confidence: 83%
“…While bursa weights of normal chicks fed T 3 or T 4 were increased, T 4 and T 3 supplementation to dwarfs increased and decreased bursa weight, respectively 1984 b). The lack of a correlated response in SRBC titers is not surprising because the relationship of SRBC antibody levels with thymic and bursal weight has been equivocal (Y AMAMOTO & G LICK , 1982 ;U BOSI et al, 1985 …”
Section: B)mentioning
confidence: 99%
“…Humoral immune response: To monitor humoral immune response, the antibodies level against sheep red blood cells (SRBCs) was quantified by following the method of Yamamoto and Glick (1982) with certain changes as described by Qureshi and Havenstein (1994). Briefly, chickens were injected through intramuscular route with SRBCs (5%; 1 mL/chicken) after 14 th day of beta-glucans administration.…”
Section: Immunological Evaluationmentioning
confidence: 99%